2009
DOI: 10.1002/pola.23613
|View full text |Cite
|
Sign up to set email alerts
|

Novel anionic polyaddition of 2‐trifluoromethylacrylate by double Michael reaction with ethyl cyanoacetate

Abstract: Novel fluorinated polymer synthesis with anionic polyaddition by double Michael addition reaction of 2‐trifluoromethylacrylate derivatives with ethyl cyanoacetate (ECA) was proposed. Diaddition product of ECA with phenyl 2‐trifluoromethylacrylate was yielded in high yield by the catalysis of sodium ethoxide in tetrahydrofuran at 60 °C. Sodium hydroxide catalyzed double Michael addition reaction also produced diaddition product in high yield. Novel anionic polyaddition of 1,4‐phenylene bis(2‐trifluoromethylacry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 50 publications
(76 reference statements)
0
12
0
Order By: Relevance
“…Acrylonitrile and methyl vinyl ketone show the high reactivity to the carbanion to yield double Michael addition products with active methylene compounds such as diethyl malonate and ethyl cyanoacetate [NCCH 2 COOC 2 H 5 ] (ECA) which work as difunctional compounds under specific reaction conditions. The high reactivity of 2-trifluoromethylacrylates as an anion acceptor might be developed to the preparation of polymers by the double Michael reaction [20].…”
Section: Anionic Addition and Polyaddition Of 2-trifluoromethylacrylatementioning
confidence: 99%
“…Acrylonitrile and methyl vinyl ketone show the high reactivity to the carbanion to yield double Michael addition products with active methylene compounds such as diethyl malonate and ethyl cyanoacetate [NCCH 2 COOC 2 H 5 ] (ECA) which work as difunctional compounds under specific reaction conditions. The high reactivity of 2-trifluoromethylacrylates as an anion acceptor might be developed to the preparation of polymers by the double Michael reaction [20].…”
Section: Anionic Addition and Polyaddition Of 2-trifluoromethylacrylatementioning
confidence: 99%
“…The high reactivity of 2-trifluoromethylacrylate as an anion acceptor might make this reaction an appropriate candidate for the preparation of polymers by the double Michael addition. 5,9 The reaction of phenyl 2-trifluoromethylacrylate (CH 2 ¼C(CF 3 ) COOC 6 H 5 ) with ECA was investigated as a model reaction catalyzed by sodium ethoxide or sodium hydroxide in the presence of excess ECA at 60 1C for 24 h. The results showed that the di-addition compound of ECA was produced in high yields. Table 5 shows the results of the novel anionic polyaddition of 1,4-phenylene bis(2-trifluoromethylacrylate) (CH 2 ¼C(CF 3 )COO-C 6 H 4 -OCOC(CF 3 )¼CH 2 ) with ECA.…”
Section: Anionic Polyaddition Of 2-trifluoromethylacrylatementioning
confidence: 98%
“…Table 5 shows the results of the novel anionic polyaddition of 1,4-phenylene bis(2-trifluoromethylacrylate) (CH 2 ¼C(CF 3 )COO-C 6 H 4 -OCOC(CF 3 )¼CH 2 ) with ECA. 5,9 Increasing the amount of ECA in the feed increases the yields and molecular weights of the polymers obtained (runs 1, 4, 6 and 10) catalyzed by sodium ethoxide in ethanol. The yield and the molecular weight of the resulting polymer are satisfactorily high when ECA is present in significant excess in the feed (run 9).…”
Section: Anionic Polyaddition Of 2-trifluoromethylacrylatementioning
confidence: 99%
See 2 more Smart Citations